Influence of indium addition on characteristics of Sn-0.3Ag-0.7Cu solder alloy - Kanlayasiri, Kannachai; Mongkolwongrojn, Mongkol; Ariga, Tadashi (My University, 2009)
Effects of indium (In) addition on solidus and liquidus temperatures, wetting time, wetting force, tensile strength, and microhardness of Sn-0.3Ag-0.7Cu lead-free solder alloy were investigated in this paper. Indium was added and varied from 0 to 3 wt%. It is found that solidus and liquidus temperatures of the solder alloy are lowered as the In content is increased. However, In also increases the melting range between solidus and liquidus temperatures. Wetting time of the solder alloy is reduced by the addition of In while the wetting force is increased with the increase of In content. With the addition of In, the Sn-rich phase is smaller in size, and the intermetallic compounds are more uniformly distributed. As a result, tensile strength and microhardness of Sn-0.3Ag-0.7Cu are increased when In is added into the solder alloy. © 2009 Elsevier B.V. All rights reserved.
Keywords: Mechanical properties; Metals and alloys; Microstructure